GAMBARAN KEPUASAN PASIEN PESERTA BPJS TENTANG PELAYANAN BPJS RUJUK BALIK DI APOTEK KIMIA FARMA 295 JATIWARINGIN - Brahmono, Umul Angga; Handono, Bayu Dwi; Dimaswara, Yogi (Jurnal Riset Kefarmasian Indonesia, 2025)
The quality of health services is a factor that must be considered by hospitals and pharmacies as a means of health services. Service quality is related to the level of patient satisfaction, where if the quality of service is not good it will reduce the level of patient satisfaction and vice versa if the quality of service is stated at the perfect level, it will increase the patient's satisfaction with the services provided. Based on a preliminary survey distributed at the Kimia Farma Jatiwaringin Pharmacy to patients, it was found that 56% of patients were satisfied and 44% were dissatisfied. The purpose of this study was to determine how the description of patient satisfaction of BPJS participants with BPJS Referral services at the Kimia Farma 295 Jatiwaringin Pharmacy. This research was conducted using purposive sampling method. The results of this study of 239 respondents based on the reliability dimension got satisfied results (57.32%), the responsiveness dimension got satisfied results (60.67%), the assurance dimension got satisfied results (56.07%), the empathy dimension got satisfied results (55.23%), the tangible dimension got satisfied results (55.65%). From this data it can be concluded that the percentage is in the satisfied category as much as (70.71%).